Burnout syndrome in workers of the health District 10D03 Cotacachi Cantón - Imbabura Workers - Encalada Echeverria, María Fernanda (2024)
The main objective of this investigation was to describe the presence of Burnout Syndrome in the medical staff of the Asdrúbal de la Torre Hospital and the administrative staff of the Health District 10D03 Cotacachi in relation to their jobs, a non-probabilistic quantitative study was carried out, where the data of 80 people were collected, of which 37 were administrative and 43 operational personnel, once the investigation was completed, a low risk of developing BS was evident in the Nursing, Laboratory, Obstetrics and X-ray departments, while in the area of Hospital Management there is a tendency to develop it, the treating physicians obtained a medium range in the three scales evaluated, being the most prone, while the resident physicians already suffer from BS. In the administrative area in the Departments of Health Promotion and Equality, Planning and Single Window, there is evidence of a low probability of developing BS, in the area of Provision and quality of ICT services and technical support there is evidence of a medium probability of BS, a category described in the study is the tendency to profile 1 in which the Financial Administrative and District Management departments are found, and finally profile 1 is described where it is already evident at a critical level for the development of SB here are the Portfolio Recovery and health surveillance departments, it is not possible to show departments with profile 2 because there are no critical levels of fault.